Two brief versions of Big Five Inventory in Peruvian college students: BFI-15p y BFI-10p - Dominguez-Lara, Sergio (2018)
The aim of this study was to create two short versions (15 and 10 items) of the Big Five Inventory (BFI) with empirical and theoretical bases. Participants included 332 Peruvian university students (82.83% women), aged between 16 and 48 years (M = 20.39). The main analysis was performed using the unweighted least squares method with oblique Procrustes rotation and fully specified matrix. The analysis results showed that both brief versions had robust psychometric properties: an adequate factor structure and empirical equivalence with the original BFI. Finally, the two versions displayed acceptable reliability indexes as well (αaverage > .60). In conclusion, both versions show favorable psychometric indicators that would enable their use in basic and group research.